2018
DOI: 10.1159/000492330
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Urgency in the Elderly

Abstract: The last 2 decades have brought an explosion of research, new products, and general attention to the problem of urinary urgency, and yet patients continue to be plagued by this symptom – especially the elderly. What is it? What does it mean? How can we guide patients successfully through this challenge? This paper presents a review of current thinking about urgency relevant to the practicing clinician, including the epidemiology, pathophysiology, evaluation, and treatment of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…(3), and symptoms are more likely to happen in elderly people (4). Although OAB is idiopathic, changes induced by aging such as estrogen deprivation (which leads to alterations in bladder function), neurological changes (which lead to changes in bladder sensation, making urgency more perceptive), and anatomic changes (which decrease bladder capacity, detrusor contractility and flow rates) predispose patients to OAB; for this reason, approximately 45% of women aged 65 or more present with the syndrome (5).…”
Section: ' Introductionmentioning
confidence: 99%
“…(3), and symptoms are more likely to happen in elderly people (4). Although OAB is idiopathic, changes induced by aging such as estrogen deprivation (which leads to alterations in bladder function), neurological changes (which lead to changes in bladder sensation, making urgency more perceptive), and anatomic changes (which decrease bladder capacity, detrusor contractility and flow rates) predispose patients to OAB; for this reason, approximately 45% of women aged 65 or more present with the syndrome (5).…”
Section: ' Introductionmentioning
confidence: 99%
“…In the BACH (Boston Area Community Health) survey, aging was a risk factor for nocturia, with a prevalence rate of 41.2% in patients aged 60 to 79 years. A prior study revealed a similar finding of markedly increasing prevalence of OAB in men and women with advanced age [15]. Regardless of health status, circulatory dynamics, organ function, and immune competency tend to decline with aging, resulting in a potentiation of OAB symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…Overactive bladder syndrome (OAB) is defined as urinary urgency, usually with urinary frequency and nocturia, with or without urgency urinary incontinence (UUI) 1,2 . The prevalence of OAB increases with age in both men and women 3 …”
Section: Introductionmentioning
confidence: 99%